Multi-phonon γ vibrational bands and chiral vibrations in the A∼100 neutron-rich region - Wang E.H.; Abushawish M.; Hamilton J.H.; Dudouet J.; Navin A.; Bhattacharyya S.; Stezowski O.; Bhat G.; Sheikh J.A.; Jehangir S.; Rejmund M.; Lemasson A.; et al. (EPJ Web of Conferences)
We present experimental evidence for the one- and two-phonon γ vibrational bands in the isotopes 103−108Mo by analyzing high-statistics γ-γ-γ and γ-γ-γ-γ coincidence data from the spontaneous fission of 252Cf. The consistency of the one- and two-phonon γ bands in both odd- and even-mass isotopes within this range provides a robust test for microscopic theories. Additionally, we have identified evidence for one-, two-, and possibly three-phonon γ bands in 103,105Nb. Triaxial projected shell model calculations successfully reproduce the level structures and align well with the excitation energies of the observed one- and two-phonon γ bands. The potential existence of three-phonon γ bands in 103,105Nb is further supported by recent particle-vibration coupling model calculations. Furthermore, chiral vibrational bands have been observed in 104,106Mo.